Meningkatkan Kemandirian Keluarga pada Klien Tuberculosis Paru Melalui Peran Tugas Kesehatan Keluarga - Sudirman, Andi Nur Aina; Mulyono, Sigit; Khasanah, Uswatul (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Tuberculosis (TB) is still one of the ten leading causes ofdeath worldwide. Ten million people are falling illdue to TB, and one and a half million people die every year, so TB is a world-famous infectious disease.Pulmonary TB is still a problem that is difficult for the government to handle. Various efforts to overcomeand overcome TB. The task offamily health is one ofthe interventions in treating clients with pulmonary TB.The purpose of this study is to determine the effect ofthe implementation of family health tasks on the level ofindependence of the client's family with pulmonary TB in the working area of Telaga Biru Health Center.This research is a quantitative study with pre-test and post-test with control group design. The population inthis study were families with pulmonary TB. The sampling technique uses probability sampling with a clustersampling technique. The number of samples used was twenty family intervention groups and twenty controlgroup families, a total sample offorty families. This study has passed the ethical test of the ethics committeeof nursing research at the Faculty of Nursing at the University ofMuhammadiyah Jakarta with no. 0191/F.9-UMJ/II 2019. Data analysis uses the paired t-test and independent t-test. The results of this study found themajority of respondents characteristics by type of adult age late 36-45 years (32.5%), female sex(67.5%), low level of education (60%).